Integrating Inductive Reasoning to Enhance Conceptual Understanding of Kinematics (Uniform Linear Motion) - T W, Alhidayatuddiniyah; Hidayat, Nandang (UNIVERSITAS INDRAPRASTA PGRI, 2025)
This research aims at the effectiveness of inductive reasoning in increasing students' understanding of the concept of Uniform Linear Motion (ULM) by integrating understanding of the philosophy of science as an effort to deepen students' scientific reasoning through the process of direct observation, collecting empirical data, and drawing conclusions independently. The research method used is a quasi-experimental method with a non-equivalent control group design, the research sample consisted 0f 60 students with a sample of two groups of Motion Physics class students, namely the experimental group taught using an inductive approach, and the control group using conventional deductive-based methods. The results of the descriptive analysis showed that there was an increase in the average post-test score with an increase of 9.97 points. Inferential analysis using the t-test showed t = 7.07 with p < 0.05, which indicated a significant difference between the two groups. These results strengthen that the inductive approach is more effective in increasing understanding of the uniform linear motion concept. This finding reinforces the effectiveness of the inductive approach, which can serve as a reference in designing more learner-centered instructional strategies.